The effect of COVID-19 on medical students’ education and wellbeing: a cross-sectional survey - ElHawary, Hassan; Salimi, Ali; Barone, Natasha; Alam, Peter; Thibaudeau, Stephanie (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Background: Canadian medical school curriculums have undergone major restructuring during the COVID-19 pandemic. This study’s goal was to assess the perceived impact of COVID-19 on medical students’ education and wellbeing.  Methods: An online survey was distributed to Canadian medical students.  Descriptive analyses and ANOVAs were used to assess changes in mental health, health habits and quality of education during the pandemic.Results: 248 medical students from 13 schools across Canada participated in this study. 74% reported a reduction in the quality of their education since COVID-19. 58% of students found online to be inferior to in-person teaching. 65% of students had more time for wellness and leisure activities, about half of the cohort felt more depressed (48%) and lonelier (52%). Student’s overall health habits worsened after the start of the pandemic (F=37.4, p < 0.001). Alcohol drinking, time spent seated, and screen time also increased since the pandemic (p < 0.001). During the pandemic, students with a prior history of depression or anxiety expressed increased depressive symptoms (66% vs. 42%, p =0.003), increased anxiety (69% vs. 41%, p < 0001), worse sleep quality (34% vs. 18%, p = 0.031), and poorer quality of life (55% vs. 65%, p = 0.024) versus those with no prior history.Conclusion: Canadian medical student’s education and wellbeing has been negatively impacted during the pandemic.